VISUAL AESTHETICS OF ELEMENTARY SCHOOL STUDENTSâ€™ â€œBATIKâ€ DESIGN - Probosiwi, Probosiwi; Gusnanda, Koko (PrimaryEdu : Journal of Primary Education, 2020)
This paper describes the beauty of layout in the process of making "batik" motif designs for elementary school students. This article's background is the translation of the collaborative lecturer and student research results at the S1 degree. The research method used is the type of qualitative research with a descriptive approach. Subjects referred to elementary school students. Data collection techniques are doing by interview, observation, and document review. The data collection methods are presented in the instrument lattice, both interviews, observations, and document reviews. The instrument grid is broken down into instrument points. The object of research is the work of students in the form of "batik" motif designs in two-dimensional fields in local content subjects. The data analysis technique used is narrative data analysis. The results of the study explained that: (1) learning the local content of "batik" in the design material applied the basic elements and principles of fine arts; (2) the process of making "batik" designs refers to the objectification stages of art carried out by student, so that they can visualize the "batik" designs as desired.